Construction and synthesis of Prussian blue analogues@Prussian blue (PBA@PB) nano-heterojunctions for enhanced antibacterial activity - Hua Jiang; Xingchen Lu; Shiqin Wu; Suli Li; Fuxing Lin; Yuanyuan Qi; Yuanhong Li; Qingli Huang (Materials & Design, 2024)
Novel nano-heterojunctions with excellent antibacterial properties are regarded as effective alternatives to antibiotics for bacterial disinfection. Herein, we have developed a universal strategy to synthesize a series of urchin-shaped Prussian blue analogues@Prussian blue (PBA@PB) nano-heterojunctions via a facile co-precipitation route for efficient bacterial disinfection, for the first time, which could overcome the disadvantages of singe PBA or PB. The optimized PBA@PB nano-heterojunctions showed remarkable bactericidal efficiency ability against multi drug-resistant (MDR) Escherichia coli (E.coli) and methicillin-resistant Staphylococcus aureus (MRSA), (99.4% and 98.8% bactericidal ratios, respectively), attributed to their outstanding photothermal and catalytic performance. It should be emphasized that the as-prepared nano-heterojunctions also showed amazing bacterial elimination efficiency in sewage. The antibacterial mechanism was also investigated using a variety of spectroscopic and microscopic techniques. It can be attributed to the formation of unique nano-heterojunctions between PB and PBA, which improves the absorption of NIR light and facilitates the separation of generated electron-hole pairs. Therefore, the urchin-shaped PBA@PB nano-heterojunctions may be promising candidates for rapidly bacterial elimination in environmental remedy and wastewater treatment.